Nondestructive isolation of mesenchymal stem cells from bone marrow using DNA aptamers. Issue 22 (18th October 2022) - Wen, Xiaohong; Zou, Yujian; Li, Lie; Nie, Hemin; Wang, Kemin; Wang, Jie; Li, Suping; Yang, Mei; Guo, Qiuping
Abstract : Mesenchymal stem cells (MSCs) mainly found in the bone marrow of adult mammals demonstrate unique capacities of differentiating into multiple cell lineages. Abstract : Mesenchymal stem cells (MSCs) mainly found in the bone marrow of adult mammals demonstrate unique capacities of differentiating into multiple cell lineages and undifferentiated MSCs are considered an ideal source of seed cells for cell therapy and tissue engineering. However, MSCs are heterogeneous and not abundant in bone marrow, and there are few specific markers for these cells currently. Therefore, new methods to isolate and characterize MSCs are urgently required. To address the problem, we successfully developed a high-specificity aptamer, called Apt-W2, to specifically recognize mouse bone marrow mesenchymal stem cells (mBMSCs). We synthesized Apt-W2 modified magnetic beads (Apt-W2-MBs) and used them as bait to fish out the MSCs from mouse bone marrow accurately by magnetic-activated cell sorting (MACS). Next, the sorted cells could break free from the Apt-W2-MBs by the competition of C-W2 (complementary strands of Apt-W2). As a result, the sorted cells were intact, and maintained the stem cell phenotype and good proliferative ability. Simultaneously, the sorted cells showed high pluripotency to differentiate into osteoblasts, chondrocytes, and adipocytes. More importantly, the Apt-W2-MB cocktail showed a fine capture performance for MSCs (∼88.33%). This new methodological approach can greatly facilitate MSC isolation efficiently and intactly, thereby enhancing the rate of in vitro differentiation of MSC-derived cells for the emerging field of tissue engineering and regenerative medicine. This new instrumental application of aptamers is an important innovation that achieved both high efficiency and nondestructive cell sorting, opening the door to novel cell sorting approaches.